GAMBARAN STATUS GIZI PADA SISWA SEKOLAH DASAR DI DESA LAKSAMANA DAN DESA SELAT GUNTUNG KECAMATAN SABAK AUH KABUPATEN SIAK - Nadia Septi; Suyanto "; Tuti Restuastuti (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTNutritional problem is still to be one of the health problem currently encountered Indonesia. Primary school children is one of the group that is susceptible to nutritional problem, underweight and overweight. The growth of primary school children who optimal associated with providing nutrition with the right quality and quantity. The purpose of this study was to describe the nutritional status in children of primary school in Laksamana and Selat Guntung at Sabak Auh, Siak. This research is a descriptive study with cross-sectional design. Respondents in this research were students in grade 1 to grade 6 which consists of 268 people chosen by total sampling method. Data were collected by questionnaire filled out by the parents of the respondents to determine student characteristics data and calculate BMI by measuring height and weight to measure the nutritional status of students. Nutritional status is divided into malnutrition, underweight, normal, overweight and obese based on anthropometric standard with BMI/U indicator. The data showed that normal nutritional status as the highest value were 178 people (66.4%), followed by underweight nutritional status were 39 people (14.6%), obese nutritional status were 26 people (9.7%), malnutrition nutritional status were 13 people (4.9%) and obese nutritional status were 12 people (4.5%).Keywords : children of school age, nutrition, nutritional status